2021
DOI: 10.3390/cancers13174261
|View full text |Cite
|
Sign up to set email alerts
|

CD47-SIRPα Checkpoint Inhibition Enhances Neutrophil-Mediated Killing of Dinutuximab-Opsonized Neuroblastoma Cells

Abstract: High-risk neuroblastoma, especially after recurrence, still has a very low survival rate. Immune checkpoint inhibitors targeting T cells have shown remarkable clinical efficacy in adult solid tumors, but their effects in pediatric cancers have been limited so far. On the other hand, targeting myeloid immune checkpoints, such as CD47-SIPRα, provide the opportunity to enhance antitumor effects of myeloid cells, including that of neutrophils, especially in the presence of cancer-opsonizing antibodies. Disialogang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 57 publications
0
22
0
Order By: Relevance
“…In a variety of neuroblastoma cell lines, knocking down CD47 or blocking SIRPa on neutrophils increased the neutrophil-mediated ADCC induced by dinutuximab (anti-GD2 antibody). Blocking the CD47-SIRPa interaction also increased ADCC capacity in primary patientderived neuroblastoma spheroid cells as long as GD2 expression was sufficient, once again highlighting the relevance of combination therapy (Figure 4) (171,172). Furthermore, anti-CD47 monoclonal antibodies were shown to work synergistically with trastuzumab to improve neutrophil ADCC against breast cancer cell lines (28,152).…”
Section: Combining Myeloid Checkpoint Inhibition With Iga Antibodies ...mentioning
confidence: 89%
“…In a variety of neuroblastoma cell lines, knocking down CD47 or blocking SIRPa on neutrophils increased the neutrophil-mediated ADCC induced by dinutuximab (anti-GD2 antibody). Blocking the CD47-SIRPa interaction also increased ADCC capacity in primary patientderived neuroblastoma spheroid cells as long as GD2 expression was sufficient, once again highlighting the relevance of combination therapy (Figure 4) (171,172). Furthermore, anti-CD47 monoclonal antibodies were shown to work synergistically with trastuzumab to improve neutrophil ADCC against breast cancer cell lines (28,152).…”
Section: Combining Myeloid Checkpoint Inhibition With Iga Antibodies ...mentioning
confidence: 89%
“…Beyond oxidative stress, neutrophils utilize additional ammunition to kill tumor cells, including granule enzymes such as elastase ( Cui et al, 2021 ) or cathepsin-G ( Sionov et al, 2019 ). In addition, neutrophils can kill antibody-opsonized tumor cells via trogocytosis ( Bouti et al, 2021 ; Martinez Sanz et al, 2021 ; Martínez-Sanz et al, 2021 ; Matlung et al, 2018 ), which could translate to tumor-targeting antibody therapeutics. These studies suggest that harnessing neutrophil tumoricidal functions, including innate immune checkpoints ( Matlung et al, 2017 ), may help combat cancer.…”
Section: The Unheeded Complexity Of Neutrophil Heterogeneity In Cancermentioning
confidence: 99%
“…Notably, neutrophils promote almost every aspect of cancer progression, such as primary tumor growth and metastasis ( Coffelt et al, 2015 ; Cools-Lartigue et al, 2013 ; Demers et al, 2016 ; El Rayes et al, 2015 ; Engblom et al, 2017 ; Gershkovitz et al, 2018a ; Park et al, 2016 ; Quail et al, 2017 ; Yang et al, 2020 ), cancer stem cell maintenance ( Wculek and Malanchi, 2015 ), exit from dormancy and cell cycle progression ( Albrengues et al, 2018 ; Houghton et al, 2010 ; Szczerba et al, 2019 ), impaired immunosurveillance ( Casbon et al, 2015 ; Shaul et al, 2021 ; Spiegel et al, 2016 ; Veglia et al, 2019 ; Yajuk et al, 2021 ), and therapeutic resistance ( Salvagno et al, 2019 ; Siwicki et al, 2021 ; Wisdom et al, 2019 ). Nevertheless, other studies have found that neutrophils can have an anti-tumorigenic role, including cytotoxicity against tumor cells ( Bouti et al, 2021 ; Cui et al, 2021 ; Gershkovitz et al, 2018a ; Gershkovitz et al, 2018b ; Hirschhorn-Cymerman et al, 2020 ; Martinez Sanz et al, 2021 ; Martínez-Sanz et al, 2021 ; Matlung et al, 2018 ) and enhanced tumor cell clearance ( Blaisdell et al, 2015 ; Eruslanov et al, 2014 ; Singhal et al, 2016 ), particularly in early-stage disease. Given the discordant mechanisms by which neutrophils can influence cancer, it is apparent that we lack a fundamental understanding of how neutrophil biology shifts in the context of malignancy.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro, macrophages can eliminate various opsonized solid [ 159 , 160 , 161 , 162 , 163 , 164 , 165 ] and hematological cancer [ 64 , 156 , 166 , 167 ] cell types via ADCP, which can be further promoted by treatment with anti-CD47 mAbs. Similarly, anti-CD47 mAbs enhance neutrophil-mediated ADCC of solid cancers in vitro, such as neuroblastoma [ 168 ]. However, it appears that neutrophils are less capable of killing hematologic cancer cells, and blockade of the CD47-SIRPα axis with anti-CD47 mAbs is not enough to promote tumor elimination.…”
Section: Cd47-sirpα As An Innate Immune Checkpoint In Neutrophil-medi...mentioning
confidence: 99%